Developing a Framework of Government Future Flow Securitization Through Public Service Agency (Badan Layanan Umum) - I Putu Sukma Hendrawan; Bram Rahadyta; Novriandini Ermaningrum (IPTEK Journal of Proceedings Series, 2020)
There’s emerging discussion about creative financing and diversification to close the funding gap of a massive development plan, with future flow securitization is one of the candidates. Since the first transaction undertaken in the late 1980’s, future flow securitization still rarely used in Indonesia. Currently, such type of instrument was coming from the state-owned enterprise notably the state toll road enterprise securitized their future toll-road revenue flow. The Government of Indonesia could use future flow securitization as part of financing diversification, with rationalities of lowering the cost of capital through secured financing, risk-sharing to the private sector, and earmarking certain revenue for particular spending. Badan Layanan Umum/BLU (public service agency) could be the agent to conduct such financing, enabled by its characteristics of public service function mixed with corporate-like governance and also its nature of revenue center agency. The government would still be in complete control since BLU is within government arms’ length and its financial management is not separated from the general budget. This study derives the potential use of future flow securitization through BLU. From the central government financial report, we found – on an aggregate basis – that there is a proper capacity of BLU’s revenue to be securitized. This paper using qualitative method to construct a securitization-fit framework comprised of model, requirements, criteria along with features of the binding arrangement, required organizational settings, compartmentalization, and tranching.